Two consecutive heterogeneous reactions of second order in well mixed aerosol system - Kopiychenko, D.Yu.; Mchedlov-Petrossyan, P.O.; Khomenko, G.A. (Вопросы атомной науки и техники, 2007)
The dynamics of concentration changes in well-mixed systems with two consecutive heterogeneous reactions of the second order on the surface of monodisperse aerosol particles is analyzed in the case of mass transfer limitations. A self-consistent set of equations is proposed. All possible variants of concentration changes were classified. Initial concentrations and mass transfer coefficients which lead to these variants were determined. It is shown that number of possible switches increases from one in the case of one binary reaction to three for consecutive reactions of the second order. Pозглянута динаміка зміни концентрацій у повністю перемішаній системі при протіканні двох послідовних гетерогенних реакцій на поверхні монодисперсних аерозольних часток у випадку, коли масоперенос реактантів до поверхні аерозолів є процесом, що лімітує. Отримано самоузгоджену систему рівнянь, проаналізовані різні варіанти зміни концентрацій і визначені початкові умови й коефіцієнти масопереносу, що приводять до цих варіантів. Показано, що за рахунок послідовності реакцій кількість можливих перемикань зростає до трьох у порівнянні з однією бінарною реакцією. Рассмотрена динамика изменения концентраций в полностью перемешанной системе при протекании двух последовательных гетерогенных реакций на поверхности монодисперсных аэрозольных частиц в случае, когда массоперенос реактантов к поверхности аэрозолей является лимитирующим процессом. Получена самосогласованная система уравнений, проанализированы различные варианты изменения концентраций и определены начальные условия и коэффициенты массопереноса, приводящие к этим вариантам. Показано, что за счет последовательности реакций количество возможных переключений возрастает до трёх по сравнению с одной бинарной реакцией.